Conservatism and Immigration Opinion in the United States - Moore, Jonathan (My University, 2018)
The popular and academic consensus on the substance of conservative opinion on immigration is that it is universally and overwhelmingly in favor of restrictive policy, but the existence of pro-immigration figures such as George W. Bush and Ronald Reagan is one reason among many to doubt the predictive accuracy of this stereotype. I argue that part of this phenomenon can be explained by understanding the diversity of thought underlying modern conservative ideology, and that by focusing more on these values and less on big tent conservatism, better predictions can be achieved. This dissertation seeks to empirically examine the substance of conservative opinion on immigration at the mass, engaged, and elite levels, and to compare these results at every stage against the popular stereotype of these opinions. The dissertation features a three-part research design including large-n regression analysis of existing survey data for the mass level, original survey research for the engaged level, and qualitative interviews at the elite level. The results of my empirical analyses suggest that while conservatism and conservative values generally do correlate with more restrictive opinions on immigration, some conservative values like limited government are frequently associated with liberalized attitudes towards immigration. This suggests that the literature’s current dismissal of ideological values as an variable useful in explaining immigration opinion comes from measurement error (focusing on big tent ideologies like liberalism and conservatism rather than smaller component values like adherence to limited government and moral traditionalism) rather than a true insignificance of ideology itself as a useful explanatory variable in this context.
Keywords: Public Opinion; Immigration; Conservatism; Ideology